A study on prevalence of obesity and life-style behaviour among medical students - M., Anupama; Iyengar, Krishna; S. S., Rajesh; M. S., Rajanna; P., Venkatesh; Pillai, Ganesh (International Journal Of Community Medicine And Public Health, 2017)
Background: The incidence of obesity is increasing dramatically worldwide. Overweight/obesity is the fifth leading risk factor for global death. At least 2-8 million adults die each year as a result of being overweight or obese. Studies on medical students and health personnel in many countries suggested that obesity is a problem among these population groups. Methods: A cross- sectional study was conducted at a medical college in Tumkur district of Karnataka. A pre-tested questionnaire was used to collect data from 200 medical students after taking their written consent. Results: Prevalence of overweight/obesity among the students was found to be 16% as per BMI cut-off. 39% of the female and 80%of the male students had normal waist-hip ratio while 61% of the female students and 20% of the male students had a higher waist-hip ratio where the risk of developing the metabolic complications was substantially increased. However, apart from breakfast skipping, no other Life-style behaviour was found to have any significant effect on obesity in the study. Conclusions: Prevalence of overweight and obesity according to WHO classification was 14.5% and 1.5%. The study reinforces the need to encourage healthy lifestyle, healthy food habits and a physically active daily routine among medical students.